2016
DOI: 10.1155/2016/3185232
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Biomarkers Panel: New Insights in Chronic Kidney Disease

Abstract: Chronic kidney disease, despite being a “silent epidemic” disease, represents one of the main causes of mortality in general population, along with cardiovascular disease, which is the leading cause of poor prognosis for these patients. The specific objective of our study was to characterize the relationship between the inflammatory status, the bone disorders markers, and kidney failure in chronic kidney disease patient stages 2–4, in order to design a novel biomarker panel that improves early disease diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
(56 reference statements)
0
27
0
1
Order By: Relevance
“…In this scenario, a huge step forward was made by the increasing progression of omics approaches, designed for identification of biomarkers useful for early diagnostic and follow-up, thus exploring their potential for clinical implementation [ 143 , 144 ]. In the era of omics, proteomics has risen, providing novel insights into disease mechanisms and therefore holds the promise of improving the life quality of CKD patients.…”
Section: Advances In Proteomic Approaches In Searching For An Ideamentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, a huge step forward was made by the increasing progression of omics approaches, designed for identification of biomarkers useful for early diagnostic and follow-up, thus exploring their potential for clinical implementation [ 143 , 144 ]. In the era of omics, proteomics has risen, providing novel insights into disease mechanisms and therefore holds the promise of improving the life quality of CKD patients.…”
Section: Advances In Proteomic Approaches In Searching For An Ideamentioning
confidence: 99%
“…Assessing various biomarkers on multiplex proteomic platforms (Luminex xMAP array, microarrays, etc.) could unravel novel insights in deciphering the disease-specific molecular mechanisms, offering panels of biomarkers for improving the diagnosis and therapy towards a personalized approach [ 143 , 145 147 ]. In the context of CKD and renal diseases, various proteomic studies have been designed, and the results were promising.…”
Section: Advances In Proteomic Approaches In Searching For An Ideamentioning
confidence: 99%
“…OPG, OPN, and FGF23 could also reflect vascular severity, the leading complication of CKD. Therefore, these studies provide a novel tool for clinical evaluation for CKD staging and therapeutic response (Mihai et al, 2016).…”
Section: Proteomics/metabolomics Studies On Ckd-mbdmentioning
confidence: 99%
“…Recent studies conclude that a cross talk between inflammation, bone, vasculature, and renal function exists in CKD. In early stage 2 of CKD, an increased expression of a panel of proteomic biomarkers was observed, including IL6, TNFα, osteoprotegerin, osteocalcin, osteopontin, and FGF23, which, at a first glance, highlights the hope of improving the management of patients with CKD starting with early stages, which is an area to focus research in the near future [29]. Another study evaluating the association between kidney function, albuminuria, and biomarkers of inflammation in a large cohort of CKD patients showed that plasma levels of IL1β, IL1RA, IL6, TNFα, hsCRP, and fibrinogen were higher among participants with lower levels of estimated glomerular filtration rate (GFR).…”
Section: Introductionmentioning
confidence: 94%